A food packaging film and a method for preparing the same

CN122980231APending Publication Date: 2026-10-27XINJIANG UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610834242.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-10
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0005]为了解决现有材料在食品保鲜应用中无法同时兼顾高力学强度、优异水蒸气阻隔性、高活性(抑菌/抗氧化)以及高成膜均一性的技术问题

Benefits of technology

[0044]本发明提供一种食品包装膜及其制备方法,采用特定的成膜组合物,构建了一个致密且功能化的复合保鲜膜结构,其具有优异的力学性能和水蒸气阻隔性能,且具备良好的紫外-可见光吸收能力;同时,该食品包装膜表现出广谱且高效的抑菌性能(特别是对大肠杆菌和金黄色葡萄球菌)以及突出的抗氧化性能(DPPH自由基清除率高);将其应用于食品保鲜时,能够显著降低果蔬失重率,维持硬度,并有效延缓可溶性固形物、可滴定酸和维生素C的流失,全面提升保鲜效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The application relates to the technical field of food packaging, and provides a food packaging film and a preparation method thereof. The food packaging film comprises a framework and a film-forming composition compounded with the framework, and the film-forming composition contains polyvinyl alcohol, carboxymethyl cellulose, glycerol and purslane extract. By adopting the specific film-forming composition, a compact and functional composite preservative film structure is constructed, which has excellent mechanical properties and water vapor barrier properties, and has good ultraviolet-visible light absorption capacity. Meanwhile, the food packaging film has broad-spectrum and high-efficiency bacteriostatic performance (especially for escherichia coli and staphylococcus aureus) and outstanding antioxidant performance (high DPPH free radical scavenging rate). When the food packaging film is applied to food preservation, the fruit and vegetable weight loss rate can be significantly reduced, the hardness can be maintained, the loss of soluble solids, titratable acid and vitamin C can be effectively delayed, and the preservation effect can be comprehensively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of food packaging technology, and in particular to a food packaging film and its preparation method. Background Technology

[0002] With the development of the food industry, the demand for food preservation packaging materials is increasing. Traditional single-component film materials often have problems such as poor mechanical strength and insufficient water vapor barrier properties. They are difficult to maintain the integrity of the packaging structure during packaging, transportation and storage, and are very likely to cause rapid moisture loss from food (such as causing fruits and vegetables to lose weight and soften).

[0003] Furthermore, conventional packaging materials typically lack active preservation capabilities, failing to effectively inhibit the growth and reproduction of microorganisms and offering limited light-blocking and antioxidant properties. When food is exposed to light or oxygen, it is highly susceptible to lipid oxidation and deterioration, nutrient degradation and loss (such as vitamin C), and spoilage, severely shortening its shelf life.

[0004] Therefore, there is an urgent need in this field to develop an active composite preservation packaging material that not only has excellent mechanical properties and water vapor barrier properties, but also has good antibacterial, antioxidant and light-blocking properties, so as to comprehensively improve the preservation effect of food and extend its shelf life. Summary of the Invention

[0005] To address the technical challenge of existing materials failing to simultaneously achieve high mechanical strength, excellent water vapor barrier properties, high activity (antibacterial / antioxidant), and high film-forming uniformity in food preservation applications, this invention provides a food packaging film and its preparation method.

[0006] In a first aspect, the present invention provides a food packaging film comprising a skeleton and a film-forming composition compounded therewith, the film-forming composition containing polyvinyl alcohol, carboxymethyl cellulose, glycerol and purslane extract.

[0007] This invention utilizes a specific film-forming composition to construct a dense and functional composite preservation film structure. Specifically, purslane extract contains a large number of active small molecules such as flavonoids, which readily aggregate in conventional polymer matrices due to their molecular polarity and surface energy. CMC, with its high molecular weight and abundant polar groups such as C=O, plays a crucial role as a dispersant and stabilizer in the system. The long-chain structure of CMC can encapsulate and disperse purslane extract through steric hindrance and intermolecular non-covalent bonds (such as electrostatic interactions and van der Waals forces), preventing the self-assembly and aggregation of small molecules in the purslane extract. This significantly alleviates localized stress concentration in the food packaging film and protects the mechanical toughness of the composite material. Simultaneously, because the purslane extract is uniformly dispersed in the matrix network, its specific surface area and contact sites are maximized, allowing even a very small amount of purslane extract to exhibit a macroscopically high E. coli inhibition rate of 100% and a DPPH free radical scavenging rate (antioxidant activity) of up to 91.83%.

[0008] PVA molecules are rich in highly polar groups (such as -OH), exhibiting extremely high regularity and order. When PVA is mixed with CMC containing different polar groups (C=O), strong hydrogen bonding and electrostatic interactions occur between the macromolecular chains of both. This interaction forms a more tightly packed interpenetrating or semi-interpenetrating polymer network structure, overcoming the defects of single CMC films, such as high brittleness and difficulty in cutting, thus endowing food packaging films with extremely high basic tensile strength. At the same time, the tight arrangement of macromolecular chains reduces the free volume, greatly increasing the difficulty for water vapor molecules to penetrate the interior of the food packaging film, thereby giving the food packaging film excellent water vapor barrier properties.

[0009] Glycerin, as a small-molecule plasticizer, can insert its hydroxyl groups into the molecular chains of PVA and CMC, replacing the hydrogen bonds between polymer molecules with polymer-plasticizer hydrogen bonds. This weakens the direct forces between the PVA and CMC macromolecules, increasing the free volume and fluidity of the polymer chains. This solves the problem of excessive film hardness and brittleness caused by overly dense cross-linking of PVA and CMC or the incorporation of purslane extract. Appropriate amounts of glycerin significantly increase the elongation at break (Eb) of the food packaging film, enabling it to adapt to the complex surface requirements of fruits.

[0010] Because high concentrations of purslane extract slightly reduce the continuity of the polymer matrix, when the film-forming composition is coated onto the skeleton, it penetrates into the microfiber pores of the skeleton as a liquid matrix. During the drying and curing process, the film-forming composition undergoes secondary hydrogen bonding with the polar groups at the skeleton interface, forming a steel reinforcement (skeleton)-concrete (polymer matrix) structure. In short, the physical support of the skeleton ensures that the final product not only contains a high concentration of active molecules but also has a mechanical strength far exceeding that of food packaging films without a skeleton. Moreover, the microstructure of the skeleton combined with the dense polymer layer completely seals off the escape channels of water vapor (significantly reducing WVP), ultimately achieving excellent ultra-low weight loss in grape preservation experiments.

[0011] In some specific embodiments of the present invention, the degree of hydrolysis of the polyvinyl alcohol is 98% to 99%. The degree of hydrolysis of polyvinyl alcohol ensures that its molecular chain has a highly dense concentration of hydroxyl groups (-OH), which guarantees the ability to form a hydrogen bond network.

[0012] In some specific embodiments of the present invention, the skeleton is PLA spunbond fabric; preferably, the density of the PLA spunbond fabric is 27.6–32.4 g / m³. 2 Adding high concentrations of small-molecule purslane extract alone can lead to agglomeration, voids, or discontinuous areas within food packaging films. Studies have found that introducing a specific structural framework into the food packaging film allows the framework's fibrous network to tightly bind with the components in the film-forming composition, compensating for the localized stress concentration caused by the purslane extract. This not only significantly improves the mechanical properties (Ts and Eb) of the food packaging film but also effectively blocks water molecules through the dense composite structure, resulting in a significant reduction in the film's water vapor penetration (WVP). Preservation experiments have confirmed that it is also more conducive to freshness preservation.

[0013] In some specific embodiments of the present invention, the Mw of the carboxymethyl cellulose is 500,000 to 850,000. This CMC structure provides sufficiently long macromolecular chains, ensuring adequate physical entanglement and electrostatic forces between polymer molecules. This allows for the formation of a continuous, crack-free, and fundamentally strong complete film matrix after casting and drying.

[0014] In some specific embodiments of the present invention, the preparation of the purslane extract includes mixing purslane powder with ethanol and then performing ultrasonic extraction, distillation, and extraction.

[0015] In some specific embodiments of the present invention, the mass ratio of the skeleton to the film-forming composition is 1:(5.5 to 11.3).

[0016] In some specific embodiments of the present invention, the performance parameters of the food packaging film satisfy one or more combinations of the following conditions: (1) Tensile strength is 10.0 MPa to 20.1 MPa, and elongation at break is 83.9% to 104.0%; (2) The water vapor permeability coefficient is 1.6 × 10⁻⁶. -10 g·m / m 2 ·s·pa~2.4×10 -10 g·m / m 2 ·s·pa; (3) The ultraviolet light transmittance at a wavelength of 280 nm is 21.3% to 22.9%, and the opacity is 3.49 A / mm to 4.49 A / mm; (4) The inhibition rate against Escherichia coli is not less than 100.00%, and the inhibition rate against Staphylococcus aureus is not less than 94.7%; (5) The DPPH free radical scavenging rate is 78.8%–91.9%; (6) The moisture content is 4.2% to 6.0%, and the swelling rate is 103.8% to 122.6%.

[0017] The food packaging film possesses excellent mechanical properties and water vapor barrier properties, as well as good UV-Vis light absorption capacity. Simultaneously, it exhibits broad-spectrum and highly efficient antibacterial properties (especially against Escherichia coli and Staphylococcus aureus) and outstanding antioxidant properties (high DPPH free radical scavenging rate). When applied to food preservation, it can significantly reduce the weight loss rate of fruits and vegetables, maintain firmness, and effectively delay the loss of soluble solids, titratable acids, and vitamin C, thus comprehensively improving the preservation effect.

[0018] In a second aspect, the present invention also provides a method for preparing the food packaging film as described above, comprising: coating a film-forming liquid onto the skeleton and drying to obtain the food packaging film; wherein the film-forming liquid contains the film-forming composition; Preferably, the film-forming liquid is composed of the film-forming composition and a solvent, wherein the solvent is selected from one or a combination of two or more of water and ethanol.

[0019] In some specific embodiments of the present invention, the method for preparing the food packaging film includes: Prepare aqueous solutions containing PVA and glycerol and aqueous solutions containing CMC and glycerol; A composite membrane solution is obtained by mixing an aqueous solution containing PVA and glycerol with an aqueous solution containing CMC and glycerol. The composite membrane solution is mixed with POE to obtain the membrane-forming solution; The film-forming liquid is coated onto the skeleton and dried to obtain the food packaging film.

[0020] In some specific embodiments of the present invention, the aqueous solution containing PVA and glycerol has a PVA concentration of 7%–12% (preferably 9%) and a glycerol concentration of 5%–25% (preferably 10%). Within the low concentration range of 7%–9% (w / v), as the amount of PVA added increases, the electrostatic and hydrogen bonding interactions between its macromolecules and other components in the food packaging film (such as glycerol and CMC) are enhanced, resulting in a more compact molecular chain arrangement and a denser food packaging film structure. At this point, the tensile strength (Ts) and elongation at break (Eb) of the food packaging film are significantly improved, reaching their highest values ​​at 9%, while the water vapor barrier value (WVP) is reduced to its lowest, exhibiting optimal water vapor barrier performance. If the concentration exceeds this range to 10%–12% (w / v), solid precipitation will occur on the surface of the food packaging film, causing stress concentration and a decrease in mechanical properties; furthermore, due to the water absorption of PVA itself, excessively high concentrations will further increase the WVP, thus reducing the preservation barrier effect.

[0021] In some specific embodiments of the present invention, the aqueous solution containing CMC and glycerol has a CMC concentration of 0.5% to 1.5% by mass and a glycerol concentration of 5% to 25% by mass (preferably 10%). As the glycerol concentration increases, the intermolecular forces of the polymer decrease, the fluidity of the molecular chains increases, and the rigid structure of the food packaging film is softened. This significantly increases the elongation at break (Eb) of the food packaging film (improving toughness), but also leads to a decrease in tensile strength (Ts). If the glycerol concentration is too high, it will cause the gaps between film-forming molecules to increase, making the food packaging film structure loose and introducing too many hydrophilic groups, resulting in an excessively high water vapor transmission rate (WVP). By limiting it to 10% (w / v), the food packaging film can be given optimal flexibility and maintain good water vapor barrier properties without severely weakening its tensile strength.

[0022] In some specific embodiments of the present invention, the composite membrane solution is obtained by mixing an aqueous solution containing PVA and glycerol with an aqueous solution containing CMC and glycerol in a volume ratio of 3:7 to 7:3 (preferably 7:3); In some specific embodiments of the present invention, the mass-volume concentration of the purslane extract in the film-forming solution is 8%–12%. The purslane extract contains a large amount of flavonoids and other active substances, and the light-absorbing groups in its aromatic ring endow the food packaging film with excellent ultraviolet absorption capacity (significantly reduced 280nm transmittance). At a concentration of 12%, its DPPH free radical scavenging rate is as high as 91.83%, effectively preventing food degradation and spoilage due to light and oxidation. The purslane extract can also disrupt bacterial cell membranes. Grape preservation experiments have shown that high-concentration food packaging films can significantly reduce food weight loss and delay the decrease in hardness, soluble solids (TSS), and titratable acid (TA).

[0023] By studying the effects of different PVA dosages, different glycerol contents, and different polymer addition ratios on the performance of packaging films, this invention designed the following batches of tests: The first batch test steps are as follows: (1) Weigh PVA and dissolve it in distilled water containing 10% (w / v) GLY (glycerol). Stir the solution continuously at 600 rpm for 1 h at 90℃ until it is completely dissolved to obtain PVA solutions with PVA contents of 7% (w / v), 8% (w / v), 9% (w / v), 10% (w / v), 11% (w / v), and 12% (w / v).

[0024] Weigh out CMC and add it to distilled water containing 10% (w / v) GLY (glycerol). Heat to 50°C and stir continuously at 600 rpm for 1 hour until completely dissolved to obtain a CMC solution with a CMC content of 1% (w / v).

[0025] (2) After cooling the PVA solution and CMC solution to room temperature, mix them in a ratio of 5:5 (v / v) and heat them to 50°C. Stir continuously at 600 rpm for 2 hours to obtain the composite membrane solution.

[0026] (3) Pour the composite membrane solution onto a 23×32cm glass plate and use a scraper to spread it evenly. Then, dry it at room temperature for 12 hours and transfer it to an oven at 50℃ for 8 hours. After it is completely dried, peel off the composite membrane and store it at room temperature. The loading ratio of the composite membrane solution is 1:8.

[0027] The first batch of composite membranes were tested, and the test results are shown in Table 1 below.

[0028] Table 1

[0029] Table 1 shows that the film thickness increases with increasing PVA concentration. The Ts and Eb of the PC composite film show an upward trend followed by a downward trend. The WVP (w / v) initially decreases and then increases with increasing PVA concentration. Furthermore, due to the water absorption properties of PVA, its content further increases the film's WVP. Considering all indicators, the food packaging film with a PVA concentration of 9% (w / v) exhibits the best performance.

[0030] The second batch of tests proceeded as follows: (1) Weigh PVA and dissolve it in distilled water containing 0% (w / v), 5% (w / v), 10% (w / v), 15% (w / v), 20% (w / v), and 25% (w / v) GLY (glycerol). Stir the solution continuously at 600 rpm for 1 hour at 90°C until it is completely dissolved to obtain PVA solutions with a PVA content of 9% (w / v). Note that when the value is 0% (w / v), it means that the water does not contain glycerol.

[0031] Weigh out CMC and add it to distilled water containing 0% (w / v), 5% (w / v), 10% (w / v), 15% (w / v), 20% (w / v), and 25% (w / v) GLY (glycerol). Heat to 50°C and stir continuously at 600 rpm for 1 hour until completely dissolved to obtain a CMC solution with a CMC content of 1% (w / v). Note that when the value is 0% (w / v), it means that the water does not contain glycerol.

[0032] (2) After cooling the PVA solution and CMC solution to room temperature, mix them at a ratio of 3:7 (v / v) and heat to 50°C. Stir continuously at 600 rpm for 2 hours to obtain the composite membrane solution.

[0033] (3) Pour the composite membrane solution onto a 23×32cm glass plate and use a scraper to spread it evenly. Then, dry it at room temperature for 12 hours and transfer it to an oven at 50℃ for 8 hours. After it is completely dried, peel off the composite membrane and store it at room temperature. The loading ratio of the composite membrane solution is 1:8.

[0034] The composite membranes obtained in the second batch were tested, and the test results are shown in Table 2 below.

[0035] Table 2

[0036] As shown in Table 2, the thickness of the food packaging film increases with increasing GLY concentration. This is likely because the increased GLY content leads to a gradual increase in the intermolecular distance, thus increasing the film thickness. Furthermore, mechanical property tests revealed that the Ts (transferase strength) of the film decreased while the Eb (expiratory weight) increased with increasing GLY concentration. This is because the addition of GLY reduces intermolecular forces and increases molecular chain fluidity, softening the rigid structure of the film and thus decreasing Ts and increasing Eb. The WVP (water permeability) value of the film increases with increasing GLY concentration. This is because the addition of GLY increases the intermolecular gaps in the film-forming molecules, making the film structure more porous. Additionally, the increased hydrophilic groups in the film with increasing GLY content further enhance its moisture permeability.

[0037] The third batch of tests followed these steps: (1) Weigh PVA and dissolve it in distilled water containing 20% ​​(w / v) GLY (glycerol). Stir the solution continuously at 600 rpm for 1 h at 90℃ until it is completely dissolved to obtain a PVA solution with a PVA content of 9% (w / v).

[0038] Weigh out CMC and add it to distilled water containing 20% ​​(w / v) GLY (glycerol). Heat to 50°C and stir continuously at 600 rpm for 1 hour until completely dissolved to obtain a CMC solution with a CMC content of 1% (w / v).

[0039] (2) After cooling the PVA solution and CMC solution to room temperature, mix them at ratios of 0:10 (v / v), 3:7 (v / v), 5:5 (v / v), 7:3 (v / v), and 10:0 (v / v) and heat to 50°C. Stir continuously at 600 rpm for 2 hours to obtain the composite membrane solution. A ratio of 0:10 (v / v) means that no PVA solution is added, and the resulting membrane solution is made solely from the CMC solution using the stirring process described in this step. A ratio of 10:0 (v / v) means that no CMC solution is added, and the resulting membrane solution is made solely from the PVA solution using the stirring process described in this step.

[0040] (3) Pour the composite membrane solution onto a 23×32cm glass plate and use a scraper to spread it evenly. Then, dry it at room temperature for 12 hours and transfer it to an oven at 50℃ for 8 hours. After it is completely dried, peel off the composite membrane and store it at room temperature. The loading ratio of the composite membrane solution is 1:8.

[0041] The composite membranes obtained in the second batch were tested, and the test results are shown in Table 3 below.

[0042] Table 3

[0043] Since CMC and PVA each possess different mechanical properties, their volume ratio significantly impacts the performance of the prepared film. Because a PVA:CMC volume ratio of 0:10 results in excessively brittle food packaging films that are difficult to cut for testing, it was not included in the mechanical and WVP performance tests. The results show that the thickness of the food packaging film continuously increases with increasing PVA content, attributed to the abundant PVA macromolecules filling the film matrix. Ts and Eb also continuously increase with increasing PVA content. The increase in Ts is due to the better regularity and orderliness of the PVA structure and molecular chains, while the increase in Eb is due to the better fluidity of the PVA molecular chains. The WVP of the food packaging film decreases with increasing PVA content because the increased PVA content leads to a corresponding increase in film thickness and structural density, thus reducing WVP.

[0044] This invention provides a food packaging film and its preparation method. A specific film-forming composition is used to construct a dense and functional composite preservation film structure, which possesses excellent mechanical properties and water vapor barrier properties, as well as good UV-Vis light absorption capacity. Simultaneously, this food packaging film exhibits broad-spectrum and highly efficient antibacterial properties (especially against Escherichia coli and Staphylococcus aureus) and outstanding antioxidant properties (high DPPH free radical scavenging rate). When applied to food preservation, it can significantly reduce the weight loss rate of fruits and vegetables, maintain firmness, and effectively delay the loss of soluble solids, titratable acids, and vitamin C, comprehensively improving the preservation effect. Attached Figure Description

[0045] To more clearly illustrate the technical solutions in this invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0046] Figure 1 SEM images of food packaging films with different POE concentrations in Test Example 1 provided by the present invention, wherein (a) PC, (b) PCP8, (c) PCP10, and (d) PCP12.

[0047] Figure 2 The images shown are SEM images of different food packaging films in Test Example 1 provided by the present invention, wherein (a) to (e) are planar views and (f) to (j) are cross-sectional views.

[0048] Figure 3 FT-IR images of different food packaging films in Test Example 2 provided by the present invention.

[0049] Figure 4The effect of different POE concentrations on the WVP of food packaging film in Test Example 7 provided by the present invention, wherein, * This indicates that P < 0.05. ** This indicates that P < 0.01.

[0050] Figure 5 This is one of the test results regarding antibacterial performance in Test Example 8 provided by the present invention, where ns indicates no significant difference, PCP12-P vs PCP12.

[0051] Figure 6 This is the second test result regarding antibacterial performance in Test Example 8 provided by the present invention.

[0052] Figure 7 This is one of the test results regarding antioxidant performance in Test Example 9 provided by the present invention, where ns indicates no significant difference, PCP12-P vs PCP12.

[0053] Figure 8 This is the second test result regarding antioxidant performance in Test Example 9 provided by the present invention.

[0054] Figure 9 This is one of the test results regarding grape weight loss rate in Test Example 10 provided by the present invention, wherein (a) the trend of weight loss rate from day 0 to day 10, and (b) the weight loss rate on day 10, wherein... ** This indicates P < 0.01, vs PC - P. *** This indicates that P < 0.001, vs. blank.

[0055] Figure 10 The second result of the grape weight loss test in Test Example 10 provided by this invention includes: (a) the trend of weight loss rate from day 0 to day 10; and (b) the weight loss rate on day 10. ** This indicates P < 0.01, vs PC - P. *** This indicates that P < 0.001, vs. blank.

[0056] Figure 11 This is one of the grape firmness test results in Test Example 10 provided by the present invention; wherein, (a) the firmness change trend from day 0 to day 10, and (b) the firmness on day 10, wherein, ** This indicates P < 0.01, vs PC - P. *** This indicates that P < 0.001, vs. blank.

[0057] Figure 12 This is the second result of the grape hardness test in Test Example 10 provided by the present invention; wherein, (a) the hardness change trend from day 0 to day 10, and (b) the hardness on day 10, ** This indicates P < 0.01, vs PC - P.*** This indicates that P < 0.001, vs. blank.

[0058] Figure 13 This is one of the test results regarding grape TSS in Test Example 10 provided by the present invention, wherein (a) the trend of TSS content change from day 0 to 10, and (b) the TSS content on day 10. *** P<0.001, vs PC-P, *** P<0.001, vs. blank).

[0059] Figure 14 This is the second test result regarding grape TSS in Test Example 10 provided by the present invention, wherein (a) the trend of TSS content change from day 0 to day 10, and (b) the TSS content on day 10. *** P<0.001, vs PC-P, *** P<0.001, vs. blank).

[0060] Figure 15 This is one of the test results regarding grape TA in Test Example 10 provided by the present invention, wherein (a) the trend of TA content change from day 0 to day 10, and (b) the TA content on day 10, wherein... ** This indicates P < 0.05, vs. PC - P. *** This indicates that P < 0.001, vs. blank.

[0061] Figure 16 This is the second test result regarding grape TA in Test Example 10 provided by the present invention, wherein (a) the trend of TA content change from day 0 to day 10, and (b) the TA content on day 10. ** This indicates P < 0.05, vs PC-P. *** This indicates that P < 0.001, vs. blank.

[0062] Figure 17 This is one of the test results regarding the vitamin C content of grapes in Test Example 10 provided by the present invention, wherein (a) the trend of vitamin C content change from day 0 to day 10, and (b) the vitamin C content on day 10. * This indicates P < 0.05, vs PC-P. *** This indicates that P < 0.001, vs. blank.

[0063] Figure 18 This is the second test result regarding the vitamin C content of grapes in Test Example 10 provided by the present invention, wherein (a) the trend of vitamin C content change from day 0 to day 10, and (b) the vitamin C content on day 10. * This indicates P < 0.05, vs PC-P. *** This indicates that P < 0.001, vs. blank. Detailed Implementation

[0064] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0065] Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in this field, or in accordance with the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased through legitimate channels. The models or parameters of some of the raw materials involved in the embodiments of this invention are shown below: Preparation of POE (purslane extract): Washed and dried purslane was pulverized and passed through a 40-mesh sieve. The purslane powder was ultrasonically extracted with 70% (w / v) ethanol at a material-to-liquid ratio of 1:15. The mixture was filtered, and the filtrate was subjected to vacuum distillation in a rotary evaporator. After concentrating to a certain volume, an equal volume of petroleum ether was added for extraction once. The lower layer solution was then dried in a 60°C forced-air drying oven to obtain POE.

[0066] PLA spunbond fabric, 30g / m 2 Purchased from Quanzhou Smartin New Materials Technology Co., Ltd.

[0067] Other raw materials and equipment are shown in the table below.

[0068] Table 4

[0069] Table 5

[0070] Table 6

[0071] Table 7

[0072] In this invention, unless otherwise specified, the temperature of the environment or solution is room temperature, which is generally in the range of 20 to 30°C.

[0073] Example 1 This embodiment provides a method for preparing a food packaging film, the steps of which are as follows: (1) Weigh PVA and dissolve it in distilled water containing 10% (w / v) GLY (glycerol). Stir the solution continuously at 600 rpm for 1 h at 90°C until it is completely dissolved to obtain a PVA solution with a PVA content of 9% (w / v).

[0074] Weigh out CMC and add it to distilled water containing 10% (w / v) GLY (glycerol). Heat to 50°C and stir continuously at 600 rpm for 1 hour until completely dissolved to obtain a CMC solution with a CMC content of 1% (w / v).

[0075] (2) After cooling the PVA solution and CMC solution to room temperature, mix them at a ratio of 7:3 (v / v) and heat to 50°C. Stir continuously at 600 rpm for 2 hours to obtain the composite membrane solution. (3) Add POE to the composite membrane solution, stir continuously at 50℃ and 600rpm for 2 hours, then stir at room temperature for 5 hours to obtain a film-forming solution with POE content of 8% (w / v). Degas the prepared solution by ultrasonication for 20 minutes for later use.

[0076] (4) The PLA spunbond fabric was adhered to a 23×32cm glass plate, and the film-forming solution was poured onto its surface. The film was then scraped to a uniform thickness with a scraper. After drying at room temperature for 12 hours, it was transferred to an oven at 50℃ for 8 hours. After complete drying, a food packaging film was obtained, labeled PCP8-P. The loading ratio of the film-forming solution was 1:8.

[0077] Example 2 The only difference from Example 1 is that a film-forming solution with a POE content of 10% (w / v) is obtained in step (3). A food packaging film is obtained and labeled as PCP10-P.

[0078] Example 3 The only difference from Example 1 is that a film-forming solution with a POE content of 12% (w / v) is obtained in step (3). A food packaging film is obtained and labeled as PCP12-P.

[0079] Comparative Example 1 The only difference from Example 1 is that POE is not added in step (3), and the process is carried out only according to the stirring process and ultrasonic degassing in step (3). The resulting food packaging film is labeled PC-P.

[0080] Comparative Example 2 The only difference from Example 1 is that step (4) is as follows: The film-forming solution was poured onto a 23×32cm glass plate and spread evenly using a scraper. After drying at room temperature for 12 hours, it was transferred to an oven at 50℃ for 8 hours. Once completely dried, the composite film was peeled off and stored at room temperature. The resulting food packaging film was labeled PCP8.

[0081] Comparative Example 3 The only difference from Example 2 is that step (4) is as follows: The film-forming solution was poured onto a 23×32cm glass plate and spread evenly using a scraper. After drying at room temperature for 12 hours, it was transferred to an oven at 50℃ for 8 hours. Once completely dried, the composite film was peeled off and stored at room temperature. The resulting food packaging film was labeled PCP10.

[0082] Comparative Example 4 The only difference from Example 3 is that step (4) is as follows: The film-forming solution was poured onto a 23×32cm glass plate and spread evenly using a scraper. After drying at room temperature for 12 hours, it was transferred to an oven at 50℃ for 8 hours. Once completely dried, the composite film was peeled off and stored at room temperature. The resulting food packaging film was labeled PCP12.

[0083] Comparative Example 5 The only difference from Comparative Example 1 is that step (4) is as follows: The film-forming solution was poured onto a 23×32cm glass plate and spread evenly using a scraper. After drying at room temperature for 12 hours, it was transferred to an oven at 50℃ for 8 hours. Once completely dried, the composite film was peeled off and stored at room temperature. The resulting food packaging film was labeled PC.

[0084] Test Example 1 Morphological Characterization After cutting samples to 0.3cm × 0.3cm size and gold plating, the microstructure of the food packaging film was observed using a scanning electron microscope under an accelerating voltage of 20kV. The test results are as follows: The surface and cross-sectional properties of food packaging films were observed using SEM, and the results are as follows: Figures 1-2 As shown, the food packaging film has a smooth and flat surface without cracks, indicating that PVA and CMC have good dissolution effects and are fully integrated with GLY. Furthermore, there is no separation between the two after drying and forming the film.

[0085] Test Example 2: FT-IR Characterization To investigate the chemical composition and structure of food packaging films, the samples were characterized using FT-IR spectroscopy. Fourier transform infrared spectroscopy was employed in the wavelength range of 4000–500 cm⁻¹. -1 Inside, tests were conducted on the food packaging film.

[0086] Test results are as follows Figure 3 As shown in the figure, the characteristic peaks of PVA are 3301 cm⁻¹. -1 The absorption peak of the -OH stretching vibration at 2939 cm⁻¹ -1 CH tensile vibration absorption peak at 1416 cm⁻¹ and 1416 cm⁻¹-1 The absorption peaks of the -CH2 bending vibrations are visible on both sides; the main characteristic peak of CMC is at 1597 cm⁻¹. -1 The C=O stretching vibration absorption peak is located at 1751 cm⁻¹; the main characteristic peak of PLA is at 1751 cm⁻¹. -1 The C=O tensile vibration peak is observed at [location missing]. The FT-IR plot of PC-P contains all the characteristic peak information mentioned above, indicating the successful recombination of PVA, CMC, and PLA. Furthermore, PCP8-P, PCP10-P, and PCP12-P show peaks at 3344 cm⁻¹. -1 2939cm -1 And 1380cm -1 A characteristic PC-P absorption peak appears at 3329 cm⁻¹, and this peak increases with increasing POE concentration in the membrane. -1 The -OH stretching vibration peak at 1608 cm⁻¹ gradually broadens, indicating an increase in the number and strength of intermolecular hydrogen bonds in the film. Compared with PC-P, PCP8-P, PCP10-P, and PCP12-P show a higher peak at 1608 cm⁻¹. -1 A sharp peak appeared at the POE position, which is mainly attributed to the stretching vibration absorption peak of C=O in the POE aldehyde group. Therefore, the FT-IR experimental results indicate that POE has been successfully loaded into PC-P.

[0087] Test Example 3: Thickness and Mechanical Property Testing The thickness of food packaging film affects its mechanical properties and WVP. In addition, the film material used for food packaging should have good strength and toughness in order to maintain the integrity of the food structure during packaging, transportation and storage.

[0088] The thickness of the food packaging film was measured at five randomly selected locations on its surface using a thickness gauge (accuracy 0.001 mm). Five measurements were taken, and the average value was recorded in mm. The tensile strength (Ts) and elongation at break (Eb) of the film were measured using a universal testing machine. Each group of food packaging films was cut into 30 mm × 5 mm pieces and tightly fixed to both ends of the instrument's lever arm with a clamping distance of 10 mm. The tensile speed was set to 10.0 mm / s, and the corresponding tensile strength (Ts) and elongation at break (Eb) were recorded.

[0089] The thickness and mechanical properties of the food packaging film are shown in Table 8.

[0090] Table 8

[0091] In the table, * P <0.05, PCP8-P vs PCP8; ** P <0.01, PC-P vs PC, PCP10-P vs PCP10; *** P<0.001, PCP12-P vs PCP12.

[0092] As shown in the table, the thickness of the food packaging film increases with increasing POE concentration, mainly due to the increased POE solid content in the composite food preservation film. Measurements of the Ts and Eb of the food packaging film revealed that, compared to PC-P, the Ts of the food packaging film decreased after the addition of POE. The PCP12-P food packaging film had the lowest Ts, at 10.373 ± 0.289 MPa. This is primarily because POE has poor dispersibility in the polymer matrix, leading to agglomeration and consequently, localized stress concentration in the food packaging film. The Eb of the food packaging film initially increased and then decreased. This may be because, as a small molecule, appropriate addition of POE can enhance the fluidity and molecular mobility of the film-forming polymer chains. However, excessive POE can affect the continuous grid structure of the film-forming matrix, resulting in voids or discontinuous regions in the composite film, thus affecting the Eb. Compared with PCP8, PCP10 and PCP12 food packaging films with the same POE concentration in Chapter 3, the addition of PLA significantly improved the mechanical properties of PCP8-P, PCP10-P and PCP12-P food packaging films. This is mainly due to the good mechanical properties of PLA.

[0093] Test Example 4: Color and Optical Performance Analysis Surface color is also an important optical property of food preservation films, influencing consumers' choices of packaged foods. UV-Vis light blocking is also an ideal characteristic of food packaging films, as exposure to visible and ultraviolet light can lead to food oxidation, spoilage, nutrient loss, and off-flavors.

[0094] Three points were randomly selected from each group of food packaging films to measure the color difference using a colorimeter. A standard white plate was used as the reference sample. The brightness (L*), redness (a*), and yellowness (b*) of the samples were measured. Each film sample was measured three times, and the average value was taken. The total color difference value ( E) Calculate using the following formula: Using a UV-Vis spectrophotometer, the membrane sample was placed in the spectrophotometer's test cell, with a white plate used as a control, to determine the membrane's optical properties. The absorbance A at 600 nm was recorded. 600 The absorbance value is then converted into an opacity evaluation film opacity (T). T is calculated using the following formula: In the formula: T, opacity; A 600 absorbance at 600 nm; d, film thickness, mm; The transmittance at 280 nm and 660 nm was used to calculate the UV and visible light resistance of the food packaging film. Each film was tested three times, and the average value was taken. The test results are shown in Tables 9 and 10 below.

[0095] Table 9

[0096] In the table, ** P<0.01, PCP12-P vs PCP12; ns no significant difference, PCP12-P vs PCP12.

[0097] Table 10

[0098] As can be seen from the table above, PC-P is opaque white. After adding POE, the a*, b*, ΔE and T values ​​of the food packaging film increase with the increase of POE concentration. This is due to the influence of the color of POE itself.

[0099] T in the table 280 and T 660 The transmittance values ​​are 280nm and 660nm, representing the ultraviolet and visible light regions, respectively. Compared to PC-P, food packaging films containing POE exhibit superior UV-Vis absorption performance. This is attributed to the POE content, which contains a large number of flavonoids. These compounds have numerous light-absorbing groups in their aromatic rings, contributing to UV absorption. Therefore, POE-containing food packaging films can be used to protect food from photo-induced oxidation and degradation. Compared to PCP12 food packaging film, which has the best preservation performance, the T-value of PCP12-P food packaging film is significantly lower. The reduced transparency of the food packaging film may be due to the white nature of the PLA spunbond fabric and the relative reduction in POE remaining on the surface as some POE penetrates into the PLA fiber network. 280 The value increased significantly, T 660 The value did not change significantly.

[0100] Test Example 5: Hydrophilicity / Hydrophilicity Test The hydrophilicity or hydrophobicity of food packaging films can be determined by measuring the WCA (water content coefficient) of the film.

[0101] Each group of food packaging films was cut into 1.0cm × 1.0cm pieces. 5μL of deionized water was dropped onto the film surface, and the different film contact angles (WCA) were observed and recorded using a DCAT21 water contact angle analyzer. The test results are shown in Table 11 below.

[0102] Table 11

[0103] It can be seen that as the concentration of POE increases, the contact angle of the food packaging film gradually decreases. This is mainly because POE is a hydrophilic material, which increases the hydrophilicity of the food packaging film.

[0104] Test Example 6: Moisture Content, Swelling Rate, and Water Solubility Test Each group of food packaging films was cut into three 1cm × 1cm pieces. The initial mass of the cut samples (W1) was measured. The samples were dried in an oven (105±2℃) until constant weight. The dried films were removed and weighed (W2), then transferred to a petri dish containing 30mL of distilled water. The petri dishes were placed at room temperature (25℃) for 24 hours to reach equilibrium. After equilibrium, the films were removed, excess water was absorbed with filter paper, and the mass was measured and recorded (W3). The films were then dried again in an oven (105±2℃) until constant weight (W4). The moisture content, swelling ratio, and water solubility were calculated using the following formulas: The test results are shown in Table 12 below.

[0105] Table 12

[0106] The data above shows that, compared with PC-P food packaging film, the addition of POE reduces the moisture content of PCP12-P food packaging film, while increasing its swelling rate and water solubility. The swelling rate and water solubility of PCP12-P increased by 14.270% and 48.865%, respectively. The increased swelling rate is due to the higher POE content readily binding to hydrophobic groups in the film-forming matrix, exposing hydrophilic groups and increasing their binding sites with water molecules. The enhanced water solubility is attributed to the increased hydrophilicity of POE, which improves the water solubility of the PC-P food packaging film.

[0107] Test Example 7 WVP Test WVP is another indicator for measuring the application potential of packaging materials in the food packaging field. WVP is determined using the gravimetric method (ASTM E00996-00). 8 mL of distilled water is placed in a 10 mL centrifuge tube with an inner diameter of 14 mm. A 30 mm diameter food packaging film sample is wrapped around the bottle opening, and the opening is sealed with sealing film. The initial mass of the bottle is recorded as m1. After incubating at 25°C and 50% RH for 24 hours, the bottle is removed, weighed, and its mass is recorded as m2. WVP is calculated using the following formula: Where: m1, initial mass of the bottle, g; m2, mass of the bottle after 24 hours under certain conditions, g; d, film thickness, m; s, permeation area, m2; p, the partial vapor pressure difference between pure water and dry atmosphere at 25℃, in Pa. Test results are as follows: Figure 4 As shown.

[0108] As can be seen from the figure, PC-P food packaging film has the highest WVP value, at 2.346 × 10⁻⁶. -10 g·m / m 2 ·s·pa. After adding 12% (w / v) POE to PC-P food packaging film, the WVP decreased to 1.612×10. -10 g·m / m 2 Compared to PC, PCP8, PCP10, and PCP12 food packaging films, the four types of food packaging films laminated with PLA spunbond fabric all showed significantly improved water vapor barrier properties. This is because PVA, CMC, and POE bond well with PLA spunbond fabric, forming a film with stronger sealing properties, resulting in a lower WVP value. Furthermore, the increased thickness of the PCP-P food packaging film also contributes to the decrease in WVP.

[0109] Test Example 8 Antibacterial Performance Test Antimicrobial packaging helps prevent the growth of microorganisms on the surface of food, thereby providing better food quality and extending shelf life.

[0110] The antibacterial activity of food packaging films against *E. coli* and *S. aureus* was determined using the plate count method. 40 mg of each food packaging film was cut, sterilized under UV light, and then placed in test tubes containing 1 mL of liquid culture medium and 50 μL of bacterial suspension, respectively. The tubes were sealed with sealing film and incubated at 37°C and 120 rpm for 18 h. 100 μL of the liquid was then spread onto solid culture medium and incubated at 37°C for 15 h. Colony growth was observed and recorded.

[0111] The antibacterial effects of food packaging films on E. coli and S. aureus are as follows: Figures 5-6As shown in the figure, PC-P food packaging film showed no significant antibacterial activity. The antibacterial activity of food packaging film containing POE against E. coli and S. aureus increased with increasing POE concentration. The food packaging film with 12% (w / v) POE showed the highest antibacterial activity, with inhibition rates of 100.00% against E. coli and 94.71% against S. aureus. This is because POE has good antibacterial activity against both bacteria, and the higher the POE concentration, the stronger its ability to disrupt bacterial cell membranes. There was no significant difference in antibacterial activity between PCP12-P food packaging film and PCP12 food packaging film, indicating that the PLA spunbond fabric in PCP12-P did not affect the antibacterial activity of the composite preservation film.

[0112] Test Example 9 Antioxidant Performance Test One of the main causes of food quality deterioration is oxidative spoilage. Adding natural substances with antioxidant activity to active packaging can reduce this spoilage. The antioxidant properties of food packaging films were tested using the DPPH free radical scavenging method.

[0113] Prepare a 0.25 mg / mL DPPH ethanol solution and store it protected from light for later use. Weigh 10 mg of food packaging film, cut it into small pieces, and soak it in 5 mL of water to prepare sample solutions. Mix 2 mL of sample solution with 2 mL of DPPH solution, and measure the absorbance at 517 nm using a UV spectrophotometer. The DPPH free radical scavenging rate (k) is calculated using the following formula: In the formula: A0, absorbance of 2 mL ethanol solution + 2 mL DPPH solution; A1, absorbance of 2 mL sample solution + 2 mL DPPH solution; A2, absorbance of 2 mL sample solution + 2 mL ethanol solution.

[0114] Results of DPPH free radical scavenging rate of food packaging film as follows Figures 7-8 As shown in the figure, PC-P food packaging film has no antioxidant activity. With the POE concentration increasing from 8% (w / v) to 12% (w / v), the DPPH free radical scavenging rate of the food packaging film increased from 78.84% to 91.83%. This is because the higher the POE concentration, the more active substances with antioxidant properties there are in the PCP-P food packaging film, thus resulting in a higher DPPH free radical scavenging rate. Analysis of the antioxidant properties of PCP12-P food packaging film and PCP12 food packaging film revealed no significant difference in DPPH free radical scavenging rate between the two groups.

[0115] Test Example 10: Grape Preservation Experiment To evaluate the application potential of PCP-P food packaging film in active packaging, the freshness of grapes treated with a blank control group without packaging film and with different concentrations of POE food packaging film was evaluated.

[0116] Grape treatment: Grapes of similar size and maturity were selected and placed in polyethylene boxes, covered with food packaging film, and a control group without food packaging film was set up. Each group contained 30 grapes. A preservation experiment was conducted at 30℃ and 30%RH for 10 days. Grapes were removed and tested at 1, 6, and 10 days. The test indicators are as follows: (1) Determination of weight loss rate Weight loss rate is one of the important indicators for judging the appearance quality of grapes. The weight loss rate is measured using the difference method and calculated using the following formula: .

[0117] In the formula: m1, mass before treatment, g; m2, mass after treatment, g.

[0118] Test results are as follows Figures 9-10 As shown in the figure, the weight loss rate of each group increased with the extension of storage time during the storage process. The weight loss rate of the blank control group increased faster, while the weight loss rate of the food packaging film-treated groups increased relatively slowly, with the PCP12-P group having the lowest weight loss rate. The weight loss rate of the blank control group increased from 0% on day 1 to 17.47%, while the weight loss rate of each PCP-P group was negatively correlated with POE concentration. On day 10, the weight loss rates of the PCP8-P, PCP10-P, and PCP12-P groups were 8.954%, 7.170%, 6.694%, and 6.021%, respectively, which were significantly lower than those of the blank control group and the PC-P group at the same time point. This indicates that the PCP-P food packaging film can effectively inhibit the moisture loss of the fruit during storage, thereby reducing the weight loss of the fruit to a certain extent. At the same time, POE, as an antibacterial substance, can also effectively reduce bacterial damage to the grape skin cellulose, thereby reducing water loss. During storage, the weight loss rate of the PCP12-P group was 6.021%, which was lower than that of the PCP12 group (6.572%). This is because the addition of PLA spunbond fabric made the thickness of the PCP12-P food packaging film greater than that of the PCP12 food packaging film and the WVP less than that of the PCP food packaging film.

[0119] (2) Hardness measurement Among the preservation quality parameters, firmness is one of the important economic and sensory traits affecting the sales volume of fresh grapes. The firmness of grape berries was measured using a GY-4 fruit firmness tester. The results of changes in grape firmness during storage are as follows: Figures 11-12As shown in the figure, the overall firmness of grape samples in different treatment groups decreased during storage. The softening of grape pulp is mainly due to the hydrolysis of pectin by pectinase into pectic acid. The blank control group showed the fastest decrease in grape firmness, from an initial 9.997 N to 7.137 N on day 10. The firmness of the PCP8-P, PCP10-P, and PCP12-P groups on day 10 were 7.443 N, 8.017 N, 8.317 N, and 8.553 N, respectively, which were significantly higher than those of the blank control group and the PC-P group. With the increase of time, the firmness of grapes in all food packaging film groups decreased, possibly because the PCP-P film can inhibit the activity of pectinase and slow down the rate of decrease in grape pulp firmness. At the same time, POE, as an antibacterial substance, can prevent microbial infection of grapes and further delay the decrease in grape firmness during storage. During storage, the hardness loss rate of the PCP12-P group was 14.666%, lower than the 15.414% hardness loss rate of the PCP12 group in Chapter 3. The PCP12-P food packaging film also showed better ability to inhibit the decrease in grape hardness than the PCP12 food packaging film. This may be because the water vapor barrier properties of the PCP12-P food packaging film were improved compared to the PCP12 food packaging film after the introduction of PLA spunbond fabric.

[0120] (3) Determination of soluble solids (TSS) content The TSS content in grapes is closely related to grape maturity and respiration rate, and is also one of the main indicators for evaluating grape fruit quality. The TSS content in grapes was determined using a handheld refractometer. The TSS results are as follows: Figures 13-14 As shown in the figure, the TSS content of grapes showed an increasing trend during storage. This is because protopectin in the grape cell walls is converted into soluble sugars, and the water in the grapes gradually dissipates, leading to an increase in TSS content. At day 10, the TSS content in the food packaging film group containing POE was significantly lower than that in the control group and the PC-P group. This indicates that the PCP-P food packaging film can effectively maintain the TSS content in grapes, thereby preserving their flavor and quality. During storage, the TSS increase rate in the PCP12-P group was 12.456%, also lower than the TSS increase rate in the PCP12 group (14.805%).

[0121] (4) Determination of TA content The TA content was determined by NaOH titration.

[0122] Three grapes were selected and crushed in a mortar. Distilled water was added to a final volume of 200 mL. After standing for 10 minutes, the mixture was filtered, and 50 mL of the extract was collected. One to two drops of phenolphthalein indicator were added, and the grape extract was titrated with 0.1 mol / L NaOH standard solution. The TA content in the sample extract was obtained by calculating the volume of NaOH consumed. The TA content was calculated using the following formula, and the average value was taken: .

[0123] Where: c, concentration of NaOH solution, 0.01 mol / L; V, volume of NaOH consumed, mL; V0, total volume of sample, mL; V1, volume of sample supernatant taken during titration, mL; m, sample mass, g; conversion factor, 1 mmol NaOH is equivalent to the mass of the main acid.

[0124] The results of the effect of food packaging film on grape TA are as follows: Figures 15-16 As shown, the total ta (TA) content of grapes decreased in all groups during storage. The rate of TA content decrease in the blank control group was greater than that in the other groups. This is because the PC-P, PCP8-P, PCP10-P, and PCP12-P groups had better barrier properties than the blank control group, thus inhibiting respiration and slowing down the rate of TA content decrease. During the storage period of 0–10 days, the blank control group showed the largest decrease in TA content, followed by the PC-P group. On day 10, the food packaging film containing POE had higher TA content. The TA contents of the PCP8-P, PCP10-P, and PCP12-P groups were 0.57%, 0.599%, and 0.611%, respectively, which were significantly higher than those of the blank group and the PC-P group. This is because the food packaging film containing POE can effectively inhibit grape respiration and microbial growth and reproduction, thereby reducing the consumption of organic acids and maintaining the quality of grapes. During storage, the TA loss rate of the PCP12-P group was 18.642%, which was lower than the TA loss rate of 33.069% of the PCP12 group. The addition of PLA spunbond fabric significantly reduced the TA loss rate, mainly because the fibrous structure of PLA spunbond fabric is conducive to tight bonding with PVA, CMC and POE, thereby improving the barrier properties of PCP12 food packaging film.

[0125] (5) Determination of VC content The vitamin C content in the pulp was determined by titration with sodium 2,6-dichlorophenolindophenol. The specific method was as follows: Three grapes were selected and 20 mL of a 2% (w / v) oxalic acid solution was added to prepare a pulp. This pulp was then transferred to an Erlenmeyer flask and diluted to 200 mL with 2% (w / v) oxalic acid. The pulp was filtered. 50 mL of the filtrate was taken and titrated with a standardized sodium 2,6-dichlorophenolindophenol solution until the filtrate turned pink and remained unchanged for 15 seconds. The volume of sodium 2,6-dichlorophenolindophenol solution used was recorded. A 20 g / L oxalic acid solution was used as a blank and titrated using the same method. The vitamin C content (mg / 100g) in the pulp was calculated using the following formula. -1 ): .

[0126] Where: V, total volume of sample extract, mL; V1, volume of sodium 2,6-dichlorophenolindophenol solution consumed in sample titration, mL; V0, volume of sodium 2,6-dichlorophenolindophenol solution consumed in blank titration, mL; 1 mL of sodium 2,6-dichlorophenolindophenol solution is equivalent to the mass of ascorbic acid, mg·mL. -1 V2, the volume of the sample solution taken during titration, mL; m, the sample mass, g.

[0127] The effect of food packaging film on vitamin C content, such as Figures 17-18 As shown, during the storage period, the vitamin C content was inversely proportional to the number of storage days. The vitamin C content of grapes in the PCP12-P group was consistently higher than that of other groups. On day 10, the vitamin C content in the blank control group decreased from the initial 3.206 mg / 100g to 0.751 mg / 100g, and the vitamin C content in the PC-P group decreased from the initial 3.160 mg / 100g to 1.048 mg / 100g. However, the vitamin C contents of the PCP8, PCP10, and PCP12 groups on day 10 were 1.296 mg / 100g, 1.420 mg / 100g, and 1.560 mg / 100g, respectively, which were significantly higher than those in the blank control group and significantly higher than those in the PC group. This is mainly because POE, with its good antioxidant capacity, effectively inhibits the oxidative decomposition of vitamin C in the fruit during storage, preventing a decrease in vitamin C content. During storage, the VC loss rate of the PCP12-P group was 50.726%, which was also lower than the VC loss rate of the PCP12 group (53.937%).

[0128] The data above shows that four PCP-P food packaging films with different POE concentrations were prepared by solution casting with PLA spunbond fabric. The mechanical properties, optical properties and water vapor barrier properties of the PCP-P food packaging films were improved. The antibacterial and antioxidant properties of the PCP-P food packaging films were not significantly different from those of PCP food preservation films.

[0129] The results of the grape preservation experiment showed that, compared with the blank control group and the PC-P group, grapes treated with PCP-P food packaging film had a lower weight loss rate and higher firmness, TSS content, TA content, and VC content. Furthermore, compared with the PCP12 group with the same POE concentration, the PCP12-P food packaging film had a better preservation effect. The addition of PLA spunbond fabric effectively improved the preservation performance of the PCP12 food packaging film, effectively inhibiting the increase of TSS and the decrease in weight loss rate, firmness, TA, and VC.

[0130] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A food packaging film, characterized in that, The invention includes a framework and a film-forming composition compounded with the framework, the film-forming composition containing polyvinyl alcohol, carboxymethyl cellulose, glycerol and purslane extract.

2. The food packaging film according to claim 1, characterized in that, The degree of alcoholysis of the polyvinyl alcohol is 98% to 99%.

3. The food packaging film according to claim 1 or 2, characterized in that, The skeleton is PLA spunbond fabric; preferably, the density of the PLA spunbond fabric is 27.6–32.4 g / m³. 2 .

4. The food packaging film according to any one of claims 1 to 3, characterized in that, The Mw of the carboxymethyl cellulose is 500,000 to 850,000.

5. The food packaging film according to any one of claims 1 to 4, characterized in that, The preparation of the purslane extract includes mixing purslane powder with ethanol and then performing ultrasonic extraction, distillation, and extraction.

6. The food packaging film according to any one of claims 1 to 5, characterized in that, The mass ratio of the skeleton to the film-forming composition is 1:(5.5 to 11.3).

7. The food packaging film according to any one of claims 1 to 6, characterized in that, The performance parameters of the food packaging film meet one or more combinations of the following conditions: (1) Tensile strength is 10.0 MPa to 20.1 MPa, and elongation at break is 83.9% to 104.0%; (2) The water vapor permeability coefficient is 1.6 × 10⁻⁶. -10 g·m / m 2 ·s·pa~2.4×10 -10 g·m / m 2 ·s·pa; (3) The ultraviolet light transmittance at a wavelength of 280 nm is 21.3% to 22.9%, and the opacity is 3.49 A / mm to 4.49 A / mm; (4) The inhibition rate against Escherichia coli is not less than 100.00%, and the inhibition rate against Staphylococcus aureus is not less than 94.7%; (5) The DPPH free radical scavenging rate is 78.8%–91.9%; (6) The moisture content is 4.2% to 6.0%, and the swelling rate is 103.8% to 122.6%.

8. A method for preparing the food packaging film according to any one of claims 1 to 7, characterized in that, include: The film-forming solution is coated onto the skeleton and dried to obtain the food packaging film; The film-forming liquid contains the film-forming composition; Preferably, the film-forming liquid is composed of the film-forming composition and a solvent, wherein the solvent is selected from one or a combination of two or more of water and ethanol.

9. The method for preparing the food packaging film according to claim 8, characterized in that, include: Prepare aqueous solutions containing PVA and glycerol and aqueous solutions containing CMC and glycerol; A composite membrane solution is obtained by mixing an aqueous solution containing PVA and glycerol with an aqueous solution containing CMC and glycerol. The composite membrane solution is mixed with POE to obtain the membrane-forming solution; The film-forming liquid is coated onto the skeleton and dried to obtain the food packaging film.

10. The method for preparing the food packaging film according to claim 9, characterized in that, In the aqueous solution containing PVA and glycerol, the mass-volume concentration of PVA is 7%–12%, and the mass-volume concentration of glycerol is 5%–25%. In the aqueous solution containing CMC and glycerol, the mass-volume concentration of CMC is 0.5% to 1.5%, and the mass-volume concentration of glycerol is 5% to 25%. The composite membrane solution is obtained by mixing an aqueous solution containing PVA and glycerol with an aqueous solution containing CMC and glycerol in a volume ratio of 3:7 to 7:

3. The mass-volume concentration of the purslane extract in the film-forming solution is 8% to 12%.